162 Increasing Concentrations of Supplemental Zinc Influence Performance, Carcass Characteristics, and Trace Mineral Status of Non-implanted and Implanted Steers - Messersmith, Elizabeth M (J Anim Sci, 2021)
One hundred twenty-eight Angus-cross steers (492 ± 29 kg) were utilized in a 2 × 4 factorial to determine the effects of dietary Zn within implant strategy on performance, carcass characteristics, and Zn status. Factors included Zn supplemented at 0, 30, 100, or 150 mg/kg dry matter ([DM]; Zn0, Zn30, Zn100, Zn150, respectively) from ZnSO(4) and implant administered on d 0 as no implant (NoIMP) or Component TE-200 (TE-200; Elanco, Greenfield, IN). Cattle were stratified by bodyweight (BW) to GrowSafe equipped pens of 5 or 6 steers and assigned to pen-wide treatments (experimental unit of steer; n = 16/treatment). Steers were weighed on d -1, 0, 18, and 59 with blood collected on -1, 18, and 40. Via Proc Mixed of SAS, linear and quadratic effects of Zn within implant treatments and assessment of NoIMP vs. TE-200 were tested for performance, carcass characteristics, and plasma data, with initial value covariates. Plasma Zn concentrations on d 18 and 40 linearly increased within NoIMP and TE-200 (P ≤ 0.03) and were lesser for TE-200 than NoIMP on d 18 (P = 0.001). Zinc linearly increased (P ≤ 0.002) d 18 BW and d 0–18 average daily gain (ADG). Within TE-200, Zn increased dressing percentage (P = 0.01) and tended to increase hot carcass weight (P = 0.09) linearly. Carcass-adjusted final BW and overall ADG tended to increase (P = 0.10) linearly within TE-200, with no Zn effects within NoIMP (P ≥ 0.18). Implanting increased carcass-adjusted final BW 13 kg over NoIMP (P < 0.0001). Overall feed efficiency quadratically increased within NoIMP (P = 0.01) peaking at Zn100 with no observed Zn effects within NoIMP or TE-200 for overall DM intake (P ≥ 0.15). These data suggest implant-induced growth in steers may require dietary Zn above current national recommendations.